2011
DOI: 10.1213/ane.0b013e3182042d4d
|View full text |Cite
|
Sign up to set email alerts
|

Publication Misrepresentation Among Anesthesiology Residency Applicants

Abstract: Misrepresented publications were fairly common among anesthesiology residency applicants. However, only a small percentage of applicants listed misrepresented publications that were clearly fraudulent or contained a citation error that conferred a competitive advantage. Identification of fraudulent publications on Electronic Residency Application Service applications is important to maintain the integrity of the application process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…Previously, Neuman et al. [11] documented that 37% of medical students applying to an anesthesia residency program reported research completion, whereas in this study, 59% of MPM fellowship applicants reported having conducted research, a difference of 22%. This may be related to an effort by applicants to demonstrate interest, gain knowledge, and make connections within the field when anticipating application to a fellowship.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Previously, Neuman et al. [11] documented that 37% of medical students applying to an anesthesia residency program reported research completion, whereas in this study, 59% of MPM fellowship applicants reported having conducted research, a difference of 22%. This may be related to an effort by applicants to demonstrate interest, gain knowledge, and make connections within the field when anticipating application to a fellowship.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, little is known about the publication patterns of applicants to MPM fellowships. Researchers have begun to address this issue, focusing their studies primarily on medical school students applying to residency programs; [1–14] some, however, have examined the publication patterns of applicants to fellowships [15–19]. In 2011, Neuman et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional integrity is one aspect of professional behaviour that has been previously assessed and it has been suggested that the accuracy of applicants to postgraduate medical programmes in self‐reporting their scientific publication histories is representative of their professional integrity. In fact, the documented prevalence of publication misrepresentation varies widely in the literature, with estimates in several single‐institution studies across various medical disciplines ranging from 1.8% to 37.6% of residency applicants who claimed at least one publication (Table S1, online) …”
Section: Introductionmentioning
confidence: 99%
“…However, it is my belief, and this is shared by other veterinary editors, that publishing misconduct is very much a reality in the veterinary literature. Since the inception meeting of the International Association of Veterinary Editors in 2004, 8 issues of publication ethics and publication misconduct have been discussed annually and accounts of failure to declare conflict of interest, publication misrepresentation, 9 (eg, author advancing his or her name in order of authorship or worse yet, falsely claiming authorship of an verified publication or falsely claiming authorship of a nonexistent publication in a verified journal – the latter of which has affected this journal), misappropriation of authorship, and plagiarism (also encountered in this journal) was reported. Reports of data fabrication in a veterinary publication have not surfaced.…”
mentioning
confidence: 99%